2017
DOI: 10.3389/fmolb.2017.00090
|View full text |Cite
|
Sign up to set email alerts
|

Function by Structure: Spotlights on Xist Long Non-coding RNA

Abstract: Recent experimental evidence indicates that lncRNAs can act as regulatory molecules in the context of development and disease. Xist, the master regulator of X chromosome inactivation, is a classic example of how lncRNAs can exert multi-layered and fine-tuned regulatory functions, by acting as a molecular scaffold for recruitment of distinct protein factors. In this review, we discuss the methodologies employed to define Xist RNA structures and the tight interplay between structural clues and functionality of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
82
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 77 publications
0
82
0
2
Order By: Relevance
“…In the last few years, a number of Xist partners have been identified, and their specific interaction with one of the repeat modules in Xist has been characterized 6 . This has led to the establishment of a preliminary but highly interesting repeat-to-function correlation through which Xist is beginning to be better understood 15 . Here, we review the latest advances in understanding mouse Xist, highlighting important insights and raising questions that remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, a number of Xist partners have been identified, and their specific interaction with one of the repeat modules in Xist has been characterized 6 . This has led to the establishment of a preliminary but highly interesting repeat-to-function correlation through which Xist is beginning to be better understood 15 . Here, we review the latest advances in understanding mouse Xist, highlighting important insights and raising questions that remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches have been especially important for understanding noncoding RNAs such as ribosomal RNAs (Lempereur et al 1985;Moazed et al 1986), spliceosomes (Black and Pinto 1989;Murphy and Cech 1993), and 7SK (Wassarman and Steitz 1991). The development of more sensitive and scalable approaches to RNA probing have made these experiments particularly useful for larger RNAs such as the long noncoding RNA (lncRNA) Xist (Maenner et al 2010;Fang et al 2015;Smola et al 2016;Liu et al 2017;Pintacuda et al 2017), which are not readily amenable to structure determination by other means.…”
Section: Introductionmentioning
confidence: 99%
“…X‐inactive specific transcript (Xist) is one of the first discovered and most well characterized lncRNAs (Pintacuda, Young, & Cerase, ; Simon et al, ). Xist functions as the major effector of the X chromosome inactivation (XCI) process in mammals and has been implicated in oncogenic processes (Fang, Sun, & Gong, ; Lee & Bartolomei, ; Plath, Mlynarczyk‐Evans, Nusinow, & Panning, ).…”
Section: Underexplored Mammalian Rna Targets For Small Molecule Intermentioning
confidence: 99%
“…Importantly, mutational studies revealed that specific structural domains, namely six tandem hairpin repeats (A–F) are crucial for its function in XCI (Wutz, Rasmussen, & Jaenisch, ). The mechanisms through which individual structural domains and protein interactions mediate the functions of Xist are currently under investigation (Pintacuda et al, ). Structural insights into the A‐ and F‐repeat region (RepA) of Xist by Pyle and co‐workers revealed an intricate tertiary architecture within specific functional modules (Liu et al, ).…”
Section: Underexplored Mammalian Rna Targets For Small Molecule Intermentioning
confidence: 99%